Emergency Food Provision for Children and Families during the COVID‐19 Pandemic: Examples from Five U.S. Cities. Issue 1 (22nd October 2020) - Jablonski, Becca B.R.; Casnovsky, Joy; Clark, Jill K.; Cleary, Rebecca; Feingold, Beth; Freedman, Darcy; Gray, Steven; Romeiko, Xiaobo; Olabisi, Laura Schmitt; Torres, Mariana; van den Berg, Alexandra E.; Walsh, Colleen; et al.
Abstract: As lockdown and school closure policies were implemented in response to the coronavirus, the federal government provided funding and relaxed its rules to support emergency food provision, but not guidance on best practices for effectiveness. Accordingly, cities developed a diverse patchwork of emergency feeding programs. This article uses qualitative data to provide insight into emergency food provision developed in five cities to serve children and families. Based on our qualitative analysis, we find that the effectiveness of local approaches appears to depend on: (i) cross‐sector collaboration, (ii) supply chains, and (iii) addressing gaps in service to increased risk populations.